TANGGUNG JAWAB HUKUM PEMEGANG SAHAM PENGENDALI ATAS KERUGIAN PERSEROAN DALAM PERUSAHAAN PERASURANSIAN INDONESIA - Bahota Silaban (jurnal.unprimdn.ac.id, 2021)
After the issurance of the Law No. 40/2014 on Insurance, insurance or reinsurance companies either conventional or sharia are obliged to stipulate minimal one control, and every control is determined by the companies to submit reports to the OJK (Financial Service Authority). In case there are other controls that have not been determined by insurance, sharia insurance, reinsurance or sharia reinsurance companies, OJK is authorized to determine a control outside the controls determined by the companies. This thesis discusses the legal liability of a controlling shareholder for the loss endured by the companies outside his control. Normative juridical approach is employed as the research method. It analyzes library materials or secondary data. This is a descriptive analytical research which analyzes the data qualitatively. The internal controlling shareholder of an insurance company has to be liable outside the shares he has for the company’s loss because of the party in his control under one condition i.e. the role of the Controlling Shareholder is proven to be liable for the loss endured by the company. It is different from the shareholder outside the controlling shareholder, referring to the Law on Limited Liability Company; he is only liable for the shares he has, yet this limited liability can be eliminated if the requirements of the company as a legal entity are not or not yet met and if there is any involvement in actions against the law. The legal principle that grounds the controlling shareholder’s legal liability for the loss endured by the company listed in the insurance companies in Indonesia is the theory of piercing the corporate veil or revealing the veil of limited liability companies i.e. a legal process that charges personal liability to the company employees, board of directors and shareholders in case of any violation done by the company.